789. Susceptibility of Phenotypic Subsets of Pseudomonas aeruginosa Isolates to Cefiderocol and Comparator Agents from SIDERO-WT 2014-2019. (4th December 2021) - Nguyen, Sean; Fam, David; Sahm, Daniel F; Hackel, Meredith; Echols, Roger; Yamano, Yoshinori
Abstract: Background: Multidrug-resistant (MDR) phenotypes are frequently observed among P. aeruginosa (PsA) isolated from hospitalized patients. This study describes the in vitro activities of cefiderocol (CFDC) and comparator agents against various non-susceptible (NS) phenotypic subsets of MDR PsA isolates from the SIDERO-WT multi-national surveillance program. Methods: Clinical PsA isolates were collected from North America (NA) and Europe in 2014-2019 and tested for susceptibility at a central laboratory. MICs (μg/ml) were determined for CFDC, ceftazidime-avibactam (CZA), ceftolozane-tazobactam (C/T), colistin, cefepime, meropenem (MEM), and ciprofloxacin by broth microdilution according to CLSI guidelines. Aztreonam-avibactam (avibactam fixed concentration of 4 µg/ml) and imipenem/relebactam (I/R) were only tested during SIDERO-WT Year 5 (i.e. 2019). Susceptibility was interpreted according to current FDA and 2021 CLSI breakpoints. Results: The different phenotypic subsets and susceptibility of tested compounds are shown in the table. Among 7700 PsA isolates, 47.7% and 23% were from respiratory and gastrointestinal sources of infection. CFDC inhibited 97.5% and 99.9% of all PsA at its FDA-S and CLSI-S MIC breakpoint of ≤1 and ≤4, respectively. CFDC had the lowest MIC90 of all tested agents and >99% S at an MIC ≤4 for all phenotypic subsets. At a MIC ≤1, CFDC displayed high susceptibility rates against all subsets including ≥88% S against CZA-NS, C/T-NS, I/R-NS, and MEM+I/R-NS isolates. Against MDR subsets, comparator agents consistently demonstrated lower activity than CFDC; 88% of MEM+C/T-NS and MEM+CZA-NS isolates had a CFDC MIC≤1 while 15.6% and 20.3% were S to I/R, respectively. 86% of MEM+CZA+C/T-NS and 80.4% CZA+C/T+I/R-NS isolates were S to CFDC. CFDC inhibited 98.1% and 99.4% of PsA isolates from NA (n = 3548) at a MIC of ≤1 and ≤4, respectively. In NA isolates that were MEM+C/T-NS; 85.7% of PsA isolates had a MIC ≤1 to CFDC and 33.3% and 28.6% were S to CZA and I/R, respectively. MEM: Meropenem; NS: Non-susceptible; CZA: Ceftazidime/avibactam; C/T: Ceftolozane/tazobactam; I/R: Imipenem/relebactam Conclusion: CFDC demonstrated potent in vitro activity against a variety of phenotypic subsets of MDR P. aeruginosa isolates as compared to agents that are commonly used to treat MDR PsA infections including strains NS to other agents. These data support the use of CFDC as an important treatment option for MDR PsA. Disclosures: Sean Nguyen, PharmD, Shionogi Inc (Employee) David Fam, PharmD, Shionogi (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Roger Echols, MD, Shionogi (Consultant) Yoshinori Yamano, PhD, Shionogi (Employee)